Telephone‐delivered individual cognitive behavioural therapy for cancer patients: An equivalence randomised trial. Issue 3 (30th January 2017) - Watson, M.; White, C.; Lynch, A.; Mohammed, K.
Abstract: Objective: To evaluate Telephone‐Delivered Cognitive Behavioural Therapy (T‐CBT) compared to CBT face to face treatment as usual (TAU‐CBT), in cancer patients with high psychological needs, in terms of mental health and coping. Method: A prospective randomised equivalence trial with Patient Reported Outcome (PRO's), measured pre‐ and post‐therapy including; Hospital Anxiety and Depression Scale (HADS), Mental Adjustment to Cancer Scale: Helpless/Hopeless subscale only (MAC H/H), Checklist of Cancer Concerns (CLCC) and the Cancer Coping Questionnaire (CCQ). A study‐specific Service Evaluation Questionnaire (SEQ) was include. Results: Assessment of change scores, in n = 118 randomised patients referred for psychological care, indicate significant improvements ( P < 0.01 or greater) for both therapy groups pre‐ and post‐therapy in HADS anxiety, depression and total scores and cancer concerns (CLCC). Overall, for the groups combined, there is a significant shift towards reduction of CCQ stress ( P = 0.028) and worry ( P = 0.003) post‐therapy when compared to baseline levels. Median number of therapy sessions was four. For cancer coping (CCQ) and for Mental Adjustment to Cancer (MAC) there were significant change scores only for Positive Focus and Helpless/hopeless scores respectively, in the TAU‐CBT group. Although equivalence was not observed, the data demonstrate that T‐CBT was non‐inferior to TAU‐CBT. Conclusions: Delivery of CBT to patients with clinician identified high need can be offered according to patient choice without loss of mental health benefit. Both TAU‐CBT and T‐CBT are effective at reducing mental health problems on the specific outcome measures.